PEMBINAAN DIGITAL MARKETING DAN PEMBUATAN RENCANA ANGGARAN BIAYA UNTUK MENINGKATKAN KETERAMPILAN BERORGANISASI PADA SISWA/I SMA PUTRA BATAM - Yvonne Wangdra; Angel Purwanti; Ronald Wangdra; Angeline Wong (ASOSIASI IDEBAHASA KEPRI, 2026)
Using social media in marketing strategies offers consumers convenience, making transactions more effective and efficient. Today, social media is not just used for social purposes but also for business and commerce, known as digital marketing, to expand marketing efforts. Besides selecting an appropriate marketing strategy, budget planning is crucial; without proper planning, it’s difficult to identify profits and make the best use of financial resources in offers or activity proposals. Preparing the RAB (Budget Plan) can be challenging, especially for large-scale activities, given their scale and cost. This coaching includes material on marketing communication, digital marketing, RAB, and Google Sites, delivered to SMA Putra Batam students. Methods include lectures and practical exercises, ensuring students understand the material, can discuss, present, and speak confidently in real situations. Evaluation of the activity measures' achievement and guidance for future improvements, conducted before, during, and after. Initially planned for five days, the activity was condensed into a single day with five sessions, attended by Year 10 IPS students in the computer lab at SMA Putra Batam Batu Aji. The Google Sites session trained students to create websites using Google Sites—an easy, quick, free tool with templates. Students were tasked with designing promotional websites creatively, supported by examples of digital marketing and simple budget planning. As a token of appreciation, they received goodie bags from volunteers after answering questions.